Mechanical and Chemical Processability of Cotton/Kapok Blends - KRISHNA PRASAD, G.; MAGESHWARAN, V.; GURUPRASAD, R.; ARPUTHARAJ, A.; SENTHILKUMAR, T.; PATIL, P. G.; JADHAV, R. K. (Cotton Research Journal, 2021)
The compact ring-spun yarns are made from cotton and natural kapok fibres and properties of blended yarn studied. Cotton/Kapok fibre blended yarns are made with two different blend proportions (80/20, 70/30) and compared with 100% cotton yarn by testing their diameter, evenness, tensile, hairiness and related chemical properties. The tensile strength of cotton/kapok blended yarn reduced with increase in the kapok content. Unevenness, hairiness, thin & thick places are higher in cotton kapok blend as compared to 100% cotton. SEM analysis showed the random distribution of kapok/cotton fibre in the yarn cross-section. However, going beyond the 30 % kapok content in the yarn resulted in difficulty in processing and higher fibre wastage was observed.